2011 Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2011
DOI: 10.1109/iembs.2011.6091423
|View full text |Cite
|
Sign up to set email alerts
|

Effect of force tightening on cable tension and displacement in greater trochanter reattachment

Abstract: The purpose of this study was to evaluate cable tension during installation, and during loading similar to walking in a cable grip type greater trochanter (GT), reattachment system. A 4th generation Sawbones composite femur with osteotomised GT was reattached with four Cable-Ready® systems (Zimmer, Warsaw, IN). Cables were tightened at 3 different target installation forces (178, 356 and 534 N) and retightened once as recommended by the manufacturer. Cables tension was continuously monitored using in-situ load… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…This was thought to be associated with the tension not being able to be checked. In a study by Canet et al, 6 trochanteric osteotomy was performed on a synthetic femur model; re-fixation of the osteotomized fragment was made with plate and cables after placement of the prosthesis, and a model was created that mimicked walking. The tension applied to the cables was at 50%, 100%, and 150% of the value recommended by the manufacturer.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This was thought to be associated with the tension not being able to be checked. In a study by Canet et al, 6 trochanteric osteotomy was performed on a synthetic femur model; re-fixation of the osteotomized fragment was made with plate and cables after placement of the prosthesis, and a model was created that mimicked walking. The tension applied to the cables was at 50%, 100%, and 150% of the value recommended by the manufacturer.…”
Section: Discussionmentioning
confidence: 99%
“… 3 , 4 Of them, while plate and cable combinations have been recounted to allow less migration and offer better stability than the horizontal cerclage wire and cable methods; studies reporting bursitis, pain, and abductor failure due to the combined use of plates and cables also exist. 1 , 2 , 4 - 6 On the other hand, some studies reported that successful clinical and radiological results have been obtained with isolated cable fixations which require less soft tissue dissection and aim at minimizing the blood supply in the osteotomized fragment. 1 , 2 , 7 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…F. Canet et al [1] analyzed the effect of force tightening and simulated walking on cable tension and displacement in trochanter reattachment with an experimental set-up. Dynamic cable load will decrease if the trochanter fracture heals.…”
Section: Introductionmentioning
confidence: 99%